2013
DOI: 10.1503/cjs.012311
|View full text |Cite
|
Sign up to set email alerts
|

Locked plate fixation of the comminuted distal fibula: a biomechanical study

Abstract: RESEARCH • RECHERCHELocked plate fixation of the comminuted distal fibula: a biomechanical study Background: The purpose of this study was to compare the biomechanical properties of locked versus nonlocked lateral fibular bridge plating of comminuted, unstable ankle fractures in a mode of catastrophic failure. Methods:We created comminuted Weber C fractures in 8 paired limbs from fresh cadavers. Fractures were plated with either standard or locked one-third tubular bridge plating techniques. Specimens were bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Multiple biomechanical studies have been performed on AO/OTA 44C-type fractures in regard to syndesmotic stability with an intact fibula [ 29 – 34 ]. There is limited literature regarding the creation and biomechanical testing of an AO/OTA 44C-type fracture with a comminuted fibula [ 35 ]. Most biomechanical models of comminuted fractures are in more distal, AO/OTA 44B-type fractures [ 35 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple biomechanical studies have been performed on AO/OTA 44C-type fractures in regard to syndesmotic stability with an intact fibula [ 29 – 34 ]. There is limited literature regarding the creation and biomechanical testing of an AO/OTA 44C-type fracture with a comminuted fibula [ 35 ]. Most biomechanical models of comminuted fractures are in more distal, AO/OTA 44B-type fractures [ 35 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…There is limited literature regarding the creation and biomechanical testing of an AO/OTA 44C-type fracture with a comminuted fibula [ 35 ]. Most biomechanical models of comminuted fractures are in more distal, AO/OTA 44B-type fractures [ 35 37 ]. Thus, in order to simulate the typical AO/OTA 44C2 fibular fracture, we marked the location of a fibular osteotomy at 7 and 8 cm proximal to the distal fibula tip and made transverse osteotomies at marked sites with an oscillating saw, removing an approximately 1-cm fibula cross section.…”
Section: Methodsmentioning
confidence: 99%
“…1,3 However, other studies have shown no biomechanical difference between the two. 17,18 In fact, Minihane et al 19 reported inferior biomechanical properties with lateral locked plating when compared with posterolateral antiglide plate fixation. The position of the posterolateral antiglide plate allowed for longer, bicortical screws through the distal fragment, improving fixation.…”
Section: Discussionmentioning
confidence: 99%
“…15,18 Conversely, those in favor of unicortical screw placement point to the possibility of intra-articular screw placement with the use of bicortical screws. 38,40 The use of an interfragmentary lag screw ( Figure 1) has been employed for increased compression and stability in oblique fibular fractures. 19,20 Lag screw only fixation of the long oblique fracture of the lateral malleolus has also been used and has demonstrated equivalency to plate fixation in young patients with good bone stock.…”
Section: Lateral Platingmentioning
confidence: 99%